Heteronuclear NMR investigations of dynamic regions of intact Escherichia coli ribosomes. - Christodoulou, J; Larsson, G; Fucini, P; Connell, SR; Pertinhez, T; Hanson, C; Redfield, C; Nierhaus, K; Robinson, C; Schleucher, J; Dobson, C (2004)
15N-(1)H NMR spectroscopy has been used to probe the dynamic properties of uniformly (15)N labeled Escherichia coli ribosomes. Despite the high molecular weight of the complex ( approximately 2.3 MDa), [(1)H-(15)N] heteronuclear single-quantum correlation spectra contain approximately 100 well resolved resonances, the majority of which arise from two of the four C-terminal domains of the stalk proteins, L7/L12. Heteronuclear pulse-field gradient NMR experiments show that the resonances arise from species with a translational diffusion constant consistent with that of the intact ribosome. Longitudinal relaxation time (T(1)) and T(1 rho) (15)N-spin relaxation measurements show that the observable domains tumble anisotropically, with an apparent rotational correlation time significantly longer than that expected for a free L7/L12 domain but much shorter than expected for a protein rigidly incorporated within the ribosomal particle. The relaxation data allow the ribosomally bound C-terminal domains to be oriented relative to the rotational diffusion tensor. Binding of elongation factor G to the ribosome results in the disappearance of the resonances of the L7/L12 domains, indicating a dramatic reduction in their mobility. This result is in agreement with cryoelectron microscopy studies showing that the ribosomal stalk assumes a single rigid orientation upon elongation factor G binding. As well as providing information about the dynamical properties of L7/L12, these results demonstrate the utility of heteronuclear NMR in the study of mobile regions of large biological complexes and form the basis for further NMR studies of functional ribosomal complexes in the context of protein synthesis.